Individual and contextual determinants of children's and adolescents' mental health care use: A systematic review. (December 2021) - Eijgermans, D.G.M.; Fang, Y.; Jansen, D.E.M.C.; Bramer, W.M.; Raat, H.; Jansen, W.
Highlights: Overall and externalising problem level determine children's mental health care use. Evidence on internalising behaviour as determinant is inconsistent. Impact/impairment is an important determinant next to the problem levels. Screening for problems is the only contextual determinant identified in children. Not living with two biological parents and previous care use determine care use. Abstract: To improve the access to children's mental health care, knowledge on the determinants of care use is important. Where previous systematic reviews mainly focus on parent-related factors, we are the first to systematically review individual and contextual determinants of mental health care use in children under the age of 18 years old. Five electronic databases were searched for studies on determinants of children's and adolescents' mental health care use. Twenty-two longitudinal, population-based, quantitative studies were included based on eight inclusion criteria. The Behavioural Model of Health Service Use by Andersen was used for data synthesis. The quality of all studies was rated as high. Seven determinants were labelled with 'good evidence' of an association in this systematic review, namely screening programs for mental health problems, family composition, previous mental health care use, overall problem level, externalising behaviour, delinquent behaviour and impact/impairment. No association was found with age, urbanisation, and somatic complaints. Evidence was inconsistent for gender, socioeconomic position, ethnic background, internalising behaviour, aggressive behaviour and depression/anxiety. Little evidence was found for 27 determinants. This systematic review found 'good evidence' for seven determinants of children's mental health care use which could be used to improve the access to care. Quality of studies, direction for future research and implications for policy and practice are discussed. More insight is needed in contextual factors and factors for which limited or inconsistent evidence was found. These insights will contribute to decreasing the discrepancies in mental health care use and facilitating earlier intervention.